Pengaruh Partisipasi Penganggaran dan Penekanan Anggaran pada Senjangan Anggaran dengan Komitmen Organisasi sebagai Variabel Pemoderasi - Widiari, Ni Nyoman Putri; Krisna Dewi, Luh Gede (E-Jurnal Akuntansi; Vol 30 No 10 (2020), 2020)
The public sector budget is an instrument of the regional government to realize growth and stability in the regional economy. This study aims to empirically examine the ability of organizational commitment to moderate the effect of budgetary participation and budgetary emphasis on budgetary slack. This research was conducted in 30 OPD Klungkung Regency. The number of samples taken was 90 people. The number of respondents analyzed was 68 people using the purposive sampling method. Data collection was carried out using a questionnaire. The data analysis technique used is the absolute difference test. Based on the results of the analysis show that organizational commitment weakens the positive influence of budgetary participation on budgetary slack and organizational commitment weakens the negative influence of budgetary emphasis on budgetary slack. Keywords: Budgeting Participation; Budget Emphasis; Organizational Commitment; Budgetary Slack.